The knockdown of stathmin with si-RNA inhibits invasion of mesothelioma - Aksoy, Asude; Varoglu, Asuman; Onalan, Ebru Etem; Tektemur, Ahmet; Artas, Gokhan; Koc, Mustafa; Ulas, Mustafa (Churchill Livingstone, 2024)
Background To investigate the mechanism of action of stathmin1 (STMN1) in mesothelioma (MSM) and whether it has any role in its treatment. Methods STMN1 expression was examined using immunohistochemistry in biopsy tissues taken from MSM patients. The relationships between the levels of STMN1 expression in the pathology preparations of MSM patients, and the clinicopathological characteristics of these patients, and their survival times were investigated. Transfection of STMN1-specific siRNA into SPC212 cells was compared to negative control siRNAs. The mRNA levels of genes that may play a role in invasion, apoptosis, and autophagy were evaluated by RT-PCR. Results The expression of STMN1 was shown to be high in MSM tissues (p < 0.05). It was found that the only independent predictor factor affecting the survival time of MSM patients was the disease stage (p < 0.05). STMN1 was significantly reduced after siRNA intervention (81.5%). STMN1 with specific siRNA has been shown to suppress invasion by reducing the mRNA levels of cadherin-6 (CDH6), fibroblast growth factor-8 (FGF8), hypoxia-inducible factor 1 (HIF1A), matrix metallopeptidase 1-2 (gelatinase A) (MMP1-2), and TIMP metallopeptidase inhibitor 2 (TIMP2), which are important markers for invasion. Although the expression of apoptosis and autophagy-related genes, caspase-2 (Casp2) and LC-3, was reduced by silencing STMN1 with specific siRNA in western blot analysis, this effect was not observed in PCR results. Conclusions Immunohistochemical analysis of STMN1 may contribute to the differential diagnosis of MSM, and STMN1 may also be considered as a potential therapeutic target in the early invasive stage of MSM therapy.
Keywords: Autophagy; Apoptosis; Mesothelioma; Invasion; Stathmin1; Survival